Stored Grain Pack Factor Measurements for Soybeans, Sorghum, Oats, Barley, and Wheat - Bhadra, Rumela; Casada, Mark E.; Turner, Aaron P.; Montross, Michael D.; Thompson, Sidney A.; McNeill, Samuel G.; Maghirang, Ronaldo G.; Boac, Josephine M. (My University, 2018)
Grain and oilseed crops stored in bins undergo compaction due to overbearing pressure of the grain inside the structure. Thus, volume measurements of grain in bins need to be combined with the amount of packing—usually called pack factor—in addition to the initial density so that the mass in the structure can be calculated. Multiple pack factor prediction methods are in use in the grain industry, but they have only been validated in the literature and compared with field data for corn and hard red winter wheat. Predictions from WPACKING, the program in ASABE standard EP413.2, and two standard USDA methods, the USDA Risk Management Agency (RMA) and USDA Farm Service Agency-Warehouse Licensing and Examination Division (FSA-W) methods, were compared to field measurements of 92 bins containing soybeans, sorghum, oats, barley, or soft white or durum wheat. The WPACKING predictions had the lowest absolute average error of predicted mass for soybeans, sorghum, barley, and wheat, while the FSA-W method had the lowest error for oats. The RMA method gave the largest prediction errors for all five crops and struggled especially with the low-density, high-compaction crops oats and barley, giving average percent absolute errors near or above 10% in both cases. Overall, WPACKING, the RMA method, and the FSA-W method had average percent absolute errors of 2.09%, 5.65%, and 3.62%, respectively, for the 92 bins. These results can be used to improve pack factor predictions for the grain industry.
Keywords: Pack factor; Stored grain inventory; Steel and concrete bins; Test weight; Soybeans; Grain sorghum